2018
DOI: 10.1108/edi-11-2017-0256
|View full text |Cite
|
Sign up to set email alerts
|

Counting heads vs making heads count

Abstract: Purpose Research on organizational diversity initiatives generally focus on either numerical diversity or racial climate. Both facets of diversity are critical, however, research has rarely examined their impact simultaneously. The paper aims to discuss these issues. Design/methodology/approach In the current study, the authors use the context of higher education, to examine how variations in the composite of numerical diversity and racial climate predict psychological disparities between faculty of color (F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Echoing this notion, Rice, Taylor, et al (2020) suggested that abusive supervision is status degrading for employees. The severe mistreatment is detrimental to employees’ beliefs that they are valuable organizational members (Rafferty & Restubog, 2011; Vogel & Mitchell, 2017) and generally has a silencing impact on employees (Kiewitz et al, 2016; Wang et al, 2020; Xu et al, 2015). This is because management research suggests abusive supervision conveys to employees that they are unimportant to the organization (Lin et al, 2013; Rafferty & Restubog, 2011; Rice, Taylor, et al, 2020; Vogel & Mitchell, 2017).…”
Section: Theory and Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Echoing this notion, Rice, Taylor, et al (2020) suggested that abusive supervision is status degrading for employees. The severe mistreatment is detrimental to employees’ beliefs that they are valuable organizational members (Rafferty & Restubog, 2011; Vogel & Mitchell, 2017) and generally has a silencing impact on employees (Kiewitz et al, 2016; Wang et al, 2020; Xu et al, 2015). This is because management research suggests abusive supervision conveys to employees that they are unimportant to the organization (Lin et al, 2013; Rafferty & Restubog, 2011; Rice, Taylor, et al, 2020; Vogel & Mitchell, 2017).…”
Section: Theory and Hypotheses Developmentmentioning
confidence: 99%
“…With respect to individual employees, "diversity climate has been called psychological diversity climate (PDC) and is the extent to which individual employees perceive that their organization and representatives of the organization value diversity and strive to create a work environment that is fair and inclusive to all employees, irrespective of their gender, ethnicity, culture or religious background" (Newman et al, 2018, p. 149). This research has revealed the significant impact of PDC on a variety of workplace outcomes (Brimhall et al, 2014;Buttner et al, 2010;Chrobot-Mason & Aramovich, 2013;Gonzalez & DeNisi, 2009;Hopkins et al, 2001;Kaplan et al, 2011;Madera et al, 2016;Newman et al, 2018;Randel et al, 2016;Vargas et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…There is no value in representational diversity if those representing are either disregarded and otherwise silenced or ostracized and excluded for initiating the change they were hired to enact (Kolowich, 2017). Authentic DEI work attends to representation, climate, and value of contribution (Vargas et al, 2018). As universities have taken steps to not only embrace but enact the values of DEI, the underbelly of unrecognized and invisible labor that has long overtaxed the too-often small number of faculty, especially women of color at historically white institutions, has been revealed (Matthew, 2016).…”
Section: The Urgency Of Nowmentioning
confidence: 99%